2021
DOI: 10.1016/j.lwt.2020.110711
|View full text |Cite
|
Sign up to set email alerts
|

Kinetic-thermodynamic study of the oxidative stability of Arbequina olive oils flavored with lemon verbena essential oil

Abstract: Arbequina extra-virgin olive oils were flavored with lemon verbena (Aloysia citrodora) essential oil (0.1-0.4%, w/ w), being evaluated quality parameters (free acidity, peroxide value, UV-extinction coefficients), oxidative stability, antioxidant and total reducing capacity. The kinetic-thermodynamic nature of the lipid oxidation was evaluated by Rancimat (110-150 • C). The essential oil addition promoted the antioxidant and total reducing capacities but, unfortunately, increased primary and secondary related … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
14
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 20 publications
(23 citation statements)
references
References 44 publications
6
14
1
Order By: Relevance
“…For the PV, the results showed a slight decreasing trend with the increase of the flavoring level allowing to admit that the addition of the EO could have a protective effect against the olive oils' oxidative degradation and rancid formation, minimizing the reaction with free oxygen. This trend was contrary to that previously observed by Cherif et al (2021) for cv. Arbequina also flavored with lemon verbena EO or in other studies (Baiano et al, 2009; Caponio et al, 2016), but similar to the trends reported by other researchers (Bobiano et al, 2019; Tarchoune et al, 2019) for different flavoring agents (e.g., fruits, leaves, dry or fresh spices, EO, or aromatic herbs).…”
Section: Resultscontrasting
confidence: 99%
See 4 more Smart Citations
“…For the PV, the results showed a slight decreasing trend with the increase of the flavoring level allowing to admit that the addition of the EO could have a protective effect against the olive oils' oxidative degradation and rancid formation, minimizing the reaction with free oxygen. This trend was contrary to that previously observed by Cherif et al (2021) for cv. Arbequina also flavored with lemon verbena EO or in other studies (Baiano et al, 2009; Caponio et al, 2016), but similar to the trends reported by other researchers (Bobiano et al, 2019; Tarchoune et al, 2019) for different flavoring agents (e.g., fruits, leaves, dry or fresh spices, EO, or aromatic herbs).…”
Section: Resultscontrasting
confidence: 99%
“…Arbequina oils' flavoring did not influence the FA, which was not affected by the different microwave heating times evaluated. These outcomes are in agreement with the previous findings of the research team (Cherif et al, 2021) and in line with the findings of Malheiro et al (2009), Cerretani et al (2009), and Yan et al (2020). Recently, Kishimoto (2019) reported that the FA of olive oils was not affected by the microwave heating time, except when an intense microwave heating was applied (i.e., heating at 500 W, reaching a temperature of 207°C), which led to an FA increase over the heating procedure.…”
Section: Resultssupporting
confidence: 93%
See 3 more Smart Citations